Strategic group formation in the Mekong Delta : - Evers, Hans-Dieter (University of Bonn, 2009)
This paper intends to analyzes recent trends of social development and water management in the Mekong Delta from a scientific approach that is based on two social theories, firstly strategic group analysis, and secondly selected core aspects of Wittfogel’s social theory of hydraulic society. By presenting recently collected data, it is illustrated how the Mekong Delta has been transformed into a modern hydraulic society, in which certain strategic groups emerged as a consequence of growing activities in hydraulic management and agricultural-based economic growth. More specifically, the paper aims to give an overview of strategic group development in the delta by putting a strong focus on the process of forming a state bureaucracy of hydraulic management and the appearance of hydraulic construction companies as its clients.